(untitled) (Research, Society and Development, 2020)
The newborn, admitted to a neonatal intensive care unit, due to his clinical severity, needs many medications; this increases the risk of problems related to drugs. The inclusion of the pharmacist in a multidisciplinary team can contribute for drug monitoring. Develop and implement a plan for pharmacist insertion in this scenario. It was developed as a work plan, and presented to service heads. The project was included in the Qualineo Program of the Ministry of Health. The pharmacist worked with an intensive care team, promoting rational use of medicines and detecting problems related to them. Initially, the pharmacist presented his objectives and how this could contribute to assist newborns. The nursing technicians had many doubts regarding drugs dilution and reconstitution that were clarified by the pharmacist. The nursing and technicians asked questions related to incompatibilities between medications, access routes and products for infusion. Doctors consulted the pharmacist about products available for prescription. The insertion in the team resulted in reduction of non-standard products; use of appropriated infusion system; reduced pharmaceutical supplies expenditure, and extension of the team’s perception. In summary, a pharmaceutical insertion in the team improved care, and promoted rational use of medicines.